Comportamiento termal de mezclas forrajeras contrastantes en sistemas lecheros de la sierra ecuatoriana. - Lascano Armas, Pola Jael (2021)
The study was developed in three dairy farms in the province of Cotopaxi, with a height ranging from 2800 to 3590 meters above sea level, in the center-north of the Callejón Interandino, located at the coordinates latitude 38.44 et and longitude -105.4965, in order to evaluate of the optimal thermal time with contrasting forage mixtures for the feeding of cows in their lactation thirds, in relation to the accumulated temperature and NDF of the pastures to have a constant quality, determine cost-benefit, animal interaction - feeding through laboratory tests and bromatological. 45 animals were selected distributed 15 in each locality with 5 in each third of lactation. An experimental investigation was applied with a completely randomized design and Tukey when there is a difference, the productive parameters in habitual management at 28, 45 and 50 days of defoliation, express negative balances of -8.16 ± 0.89, which agree with the presence of mild ketosis with a range of ketone bodies of 12.86 ± 074, NUS 19.25 ± 0.34 and mean milk production of 16.39G01; 9.99G02; 11.44G03; to the change of management with philochronous at day 20G1 with 122 ° C and FDN of 34; G2 with 214 ° C, neutral detergent fiber of 38.59 and Farm 3 with 246 ° C at 45 days and NDF of 45.3, energy balances are improved with -0.24 ± 0.01, absence of ketosis 3.30 ± 0.23, normal blood urea nitrogen 20.41 ± 0.26, better milk production at 19G01; 10.66G02 and 12.66G03 liters per day, represented in sustainability and sustainability, therefore the modeling based on this new approach that relates the FDN with the Philochron (thermal sum) seen as quality of the pastures is a useful tool to incorporate the existing grazing models.